PENGARUH PERBEDAAN JENIS UMPAN TERHADAP HASIL TANGKAPAN IKAN DENGAN MENGGUNAKAN ALAT TANGKAP BUBU DASAR (BOTTOM FISH TRAP) : The Effect Of Different Types Of Bait On Fish Catch Results Using Bottom Fish Trap - Wahidurrahman, Wahidurrahman; Sativa, Denianto Yoga; Atmanegara, Febrian Kusuma (Yayasan Al-Amin Qalbu, 2025)
The purpose of this study was to determine the Construction and operational techniques of the Bubu (fish trap) fishing gear, to determine the best types of bait in fishing activities and to determine the number and types of fish caught using the Bubu (fish trap) fishing gear. This study used an experimental method with the experimental design used was a Completely Randomized Design (CRD), then continued with the Least Significant Difference (LSD) test at 5% and 1% levels, to determine the smallest difference from each treatment. While the factors observed in this study were 3 (three) different types of bait, namely bait A: Anchovy, bait B: Lemuru Fish and bait C: Stingray. The results of the study showed that the trap given bait A (anchovy) got the most catch, which was 11.9 kg, then the second order was bait B (lemuru fish) with a catch of 7.7 kg, and the least catch was bait C (stingray). The water quality observed during the study included: water clarity ranging from 6.10 - 8.90 m, current speed ranging from 10 - 15 cm, salinity ranging from 27 - 29 ppt, temperature ranging from 29 - 30oC, the depth of the research location waters averaged 12.5 m and the sandy bottom of the waters was slightly coral. There were significant or very significant differences between each research treatment. The 5% BNT test showed a result of 0.38, meaning that X1 and X2 showed significantly different results, X1 and X3 showed significantly different results and X2 and X3 showed significantly different results